Precision Pharyngeal Flap: An Individualized, Patient-Specific Surgery for the Treatment of Velopharyngeal Insufficiency. Issue 2 (17th March 2022) - Baek, Rong-Min; Kim, Ji-Young; Kwon, Heeyeon; Ahn, Taeseon; Kim, Baek-Kyu; Myung, Yujin
Abstract : Background: The pharyngeal flap is one of the most common secondary surgeries for the correction of velopharyngeal insufficiency (VPI) for patients with cleft palate and/or cleft lip and palate. This study aimed to demonstrate the effectiveness of the precision pharyngeal flap surgery performed by the senior author. Materials and Methods: Children with VPI, who underwent precision pharyngeal flap, were retrospectively examined. All surgical procedures were performed by the senior author. The flap size was individually configured based on the patients' preoperative nasopharyngoscopic analysis and speech function evaluation. Pre- and post-operative velopharyngeal functions were assessed using perceptual speech evaluation and nasometric analysis; factors affecting surgical outcomes were determined. Results: Of 138 patients, 112 (women: 53, men: 59) were included in analyses, according to the inclusion and exclusion criteria. The median follow-up period was 21 months (range: 9–120). Postoperative perceptual speech evaluation revealed improved velopharyngeal function in 108 (96.4%). There were no reports of postoperative hyponasality (preoperative, 1.8% versus postoperative, 0%; P  = 0.053). Other parameters of perceptual speech evaluation (hypernasality, nasal emission, articulation error, and intelligibility) showed significant improvement postoperatively ( P  < 0.01). Postoperative nasalance scores revealed sufficient postoperative resonance rating in 96% of patients. No patients experienced postoperative complications (bleeding, airway obstruction, and surgical wound dehiscence). Conclusions: Individually configured pharyngeal flaps designed based on preoperative nasopharyngoscopic examination coupled with precise surgical techniques led to the high surgery success rate for VPI treatment.